Responses to COVID-19 From Non-State School Leaders in Latin America, Sub-Saharan Africa and, India: A Call for Educational Equity - Cordeiro, Paula A.; Gluckman, Maxie; Johnson, Andy (Frontiers in Education, 2021)
In early 2020, the rapid spread of the COVID-19 pandemic was an unprecedented shock to the global education system, resulting in most educational institutions closing their doors and turning to various forms of remote learning to ensure continuous education for their communities. Since the world has not experienced this scale of school closure before, the goal of this study was to explore what, if anything, non-state schools (NNSs) schools were doing to support remote learning in order to help prepare for future events that curtail education. In May 2020, Edify, an international non-governmental organization (INGO) operating in eleven nations in the Global South conducted a telephone survey with a stratified random sample of 388 school leaders. Since to what extent learning had continued across contexts was relatively unknown, the survey aimed to inform the organization’s current and future responses to the COVID-19 pandemic and potential future educational interruptions, In addition to identifying the various uses of technology and possible innovations as to how non-state schools can respond when a crisis impacts their operating status, this paper describes three areas of concern expressed by the school leaders: 1) the health and safety of children and adults in the school; 2) the various challenges of maintaining financial sustainability; and, 3) the learning loss of students due to the lack of preparedness for such a massive interruption in their school’s normal operations.